2022
DOI: 10.21203/rs.3.rs-2094373/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyfluorinated Crosslinker-based Solid Polymer Electrolytes for Long-Cycling 4.5 V Lithium Metal Batteries

Abstract: Solid polymer electrolytes (SPEs), which are favorable to form intimate interfacial contacts with electrodes, are promising electrolyte of choice for long-cycling lithium metal batteries (LMBs). However, typical SPEs with easily oxidized oxygen-bearing polar groups exhibit narrow electrochemical stability window (ESW), making it impractical to increase specific capacity and energy density of SPE based LMBs with charging cut-off voltage of 4.5 V or higher. Here, a polyfluorinated crosslinker has been applied to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The highly polar -CN in the polymer effectively reduces the electron density of its adjacent ester group (COO − ) and improves overall oxidation resistance. On the other hand, the withdrawing electron effect from -CN can suppress the frontier orbital electron from concentrating on the ester group but also distributes on AN segments 37 . Delocalization of frontier electrons is helpful for avoiding an oxidation reaction to take place on a certain position.…”
Section: Stability Of High Entropy Composite Polymer Electrolytesmentioning
confidence: 99%
“…The highly polar -CN in the polymer effectively reduces the electron density of its adjacent ester group (COO − ) and improves overall oxidation resistance. On the other hand, the withdrawing electron effect from -CN can suppress the frontier orbital electron from concentrating on the ester group but also distributes on AN segments 37 . Delocalization of frontier electrons is helpful for avoiding an oxidation reaction to take place on a certain position.…”
Section: Stability Of High Entropy Composite Polymer Electrolytesmentioning
confidence: 99%
“…19 However, the effect of high/low temperatures on polymer-based electrolytes is multidimensional, not only including the physical and electrochemical properties of electrolytes (low temperature ionic conductivity and thermal stability), but also relating to the electrodeelectrolyte interface compatibility (interface stability and destruction). [20][21][22][23] Numerous studies have attempted to overcome these limitations. For instance, Yu and coworkers demonstrated that the ionic conductivity of polymer-based electrolytes could be improved by introducing different dipoles; the asprepared poly(vinyl ethylene carbonate) (PVEC) based polymer electrolyte contained two kinds of dipoles (CQO and C-O) and achieved a high ionic conductivity of 0.4 mS cm À1 @À15 1C.…”
Section: Introductionmentioning
confidence: 99%
“…This work brings new insight on exploring superior room-temperature ionic conductors based on metal coordination compounds.Solid-state lithium-metal batteries (LMBs) comprising Li metal anode and non-combustible solid-state electrolytes (SSEs) are widely recognized as one of the most promising next-generation energy storage systems with both high energy density and superior safety [1][2][3] . As the core component, it is of critical importance to develop highperformance SSEs with high ionic conductivity, extraordinary chemical/electrochemical stability, exceptional electrode compatibility and ease of processing [4][5][6][7][8] .Generally, SSEs can be categorized into two groups: inorganic ceramic electrolytes and organic polymer electrolytes. Inorganic SSEs such as Li 10 GeP 2 S 12 (LGPS), Li 7 La 3 Zr 2 O 12 (LLZO) and Li 1+x Al x Ti 2-x (PO 4 ) 3 (LATP) typically exhibit high ionic conductivity of greater than…”
mentioning
confidence: 99%
“…Solid-state lithium-metal batteries (LMBs) comprising Li metal anode and non-combustible solid-state electrolytes (SSEs) are widely recognized as one of the most promising next-generation energy storage systems with both high energy density and superior safety [1][2][3] . As the core component, it is of critical importance to develop highperformance SSEs with high ionic conductivity, extraordinary chemical/electrochemical stability, exceptional electrode compatibility and ease of processing [4][5][6][7][8] .…”
mentioning
confidence: 99%